2014
DOI: 10.4049/jimmunol.1401136
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Deaminase Acting on RNA 1 Limits RIG-I RNA Detection and Suppresses IFN Production Responding to Viral and Endogenous RNAs

Abstract: Type I interferons (IFNs) play central roles in innate immunity; however, overproduction of IFN can lead to immunopathology. Here, we demonstrate that adenosine deaminase acting on RNA 1 (ADAR1), an RNA-editing enzyme induced by interferon, is essential for cells to avoid inappropriate sensing of cytosolic RNA in an inducible knockout cell model – the primary mouse embryo fibroblast (MEF) derived from ADAR1 lox/lox & Cre-ER mice, as well as in HEK293 cells. ADAR1 suppresses viral and cellular RNA detection by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 50 publications
(66 reference statements)
3
93
0
Order By: Relevance
“…AGS is an autosomal-recessive inflammatory disorder that affects the brain and skin and is characterized by an aberrant immune response and increased interferon-α expression 84 . Failed editing of certain endogenous dsRNAs such as Alu by the mutant ADAR1, and the consequent activation of interferon signalling, seem to underlie the pathogenesis of AGS 83,85 . Indeed, the overproduction of interferons is detected in the brains and spinal cords of conditional Adar1 -null mice 85 .…”
Section: Deficiency In A-to-i Rna Editingmentioning
confidence: 99%
“…AGS is an autosomal-recessive inflammatory disorder that affects the brain and skin and is characterized by an aberrant immune response and increased interferon-α expression 84 . Failed editing of certain endogenous dsRNAs such as Alu by the mutant ADAR1, and the consequent activation of interferon signalling, seem to underlie the pathogenesis of AGS 83,85 . Indeed, the overproduction of interferons is detected in the brains and spinal cords of conditional Adar1 -null mice 85 .…”
Section: Deficiency In A-to-i Rna Editingmentioning
confidence: 99%
“…Another feasible explanation is that the RNA binding activity of ADAR1 is involved in the suppression of IFN signaling. Recently, Yang et al demonstrated that ADAR1 binds dsRNA, thereby limiting cytosolic dsRNA sensing by RLRs [65]. In addition, ADAR1 suppresses activation of both PKR and IRF3, by a mechanism still to be resolved [66].…”
Section: Unwanted Immune Responses Induced By Mrna Recognitionmentioning
confidence: 99%
“…28,46 Sera from the conditional KO mice for ADAR1 and littermate controls were assessed for alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase, and alkaline phosphatase levels with a DRI-CHEM 4000 Chemistry Analyzer (HESKA Co., Loveland, CO).…”
Section: Mouse Modelsmentioning
confidence: 99%
“…46,55 Hepatocytes free of nonparenchymal cells were isolated from the inducible ADAR1 KO mice by two-step liver perfusion, and the cells were cultured under 56,57 Tamoxifen was added to the culture medium to induce ADAR1 gene deletion ( Figure 6A). ADAR1 gene deletion was effectively achieved by tamoxifen induction in the hepatocytes, as verified by the PCR analysis of the ADAR1 gene alleles and diminishing levels of ADAR1 protein ( Figure 6, B and C).…”
Section: Adar1 In Liver Homeostasismentioning
confidence: 99%
See 1 more Smart Citation